Reduction in Design Stability Number of Monolayer Armour Units for Singular Conditions of Projects in Rubble Mound Breakwaters - Hugo Juan Donini; Ricardo Horacio del Valle (Ingeniería del Agua)
The evaluation of concrete single layer of breakwaters is based on the application of design coefficients obtained in laboratory tests, primarily two-dimensional and under controlled conditions. With the experience of more than 30 years in structures of this type in the world, it is important to compare the values of stability numbers used in the design with those who are in breakwaters as built. In this paper, update and increase the data collected with respect to previous publications, developing an analysis of particular situations in which the amour layer stability coefficients are reduced. A series of Accropode® and Core-LocTM recommendations concerning the design elements is also made. Also there are conclusions related to increases in the volume and the reduction in the number of blocks needed for different numbers of stability proposed.